Effects of wearing and removing dentures on oropharyngeal motility during swallowing. (2nd October 2016) - Onodera, S.; Furuya, J.; Yamamoto, H.; Tamada, Y.; Kondo, H.
Summary: Wearing dentures and dysphagia are common in older individuals; however, it is still unknown how dentures affect oral and pharyngeal swallowing. The purpose of this study was to reveal the effects of wearing and removing dentures on oropharyngeal movements during pharyngeal swallowing in the feeding sequence of solid food. Participants were 25 edentulous volunteers (nine men, 16 women; mean age 76·2 years) who wore complete dentures. The test food was minced agar jelly containing barium sulphate. Subjects were instructed to feed and swallow the test food with or without dentures during observation using videofluorography. We quantitatively evaluated the range, distance and duration of oropharyngeal movements during pharyngeal swallowing. When dentures were absent, the range of mandible and hyoid movements were significantly expanded in the anterosuperior direction, and the range of laryngeal movement was significantly expanded in the anterior direction. Additionally, the posterior pharyngeal wall contraction and upper oesophageal sphincter opening significantly increased. In addition, the distances of the mandible, hyoid and laryngeal movements and the mandibular duration were significantly extended when dentures were absent. No significant differences were observed in the duration of movements of other organs between wearing and removing dentures. The hyoid bone, larynx, posterior pharyngeal wall and upper oesophageal sphincter do not change their duration of movements when dentures were removed but, rather, expand their range of movement. This might be a spatial change of oropharyngeal movement to avoid temporal changes in pharyngeal swallowing when dentures were absent in edentulous older individuals.